Smoking Cessation for Pregnant Smokers: Development and Pilot Test of an Emotion Regulation Treatment Supplement to Standard Smoking Cessation for Negative Affect Smokers. Issue 5 (11th April 2017) - Bradizza, Clara M.; Stasiewicz, Paul R.; Zhuo, Yue; Ruszczyk, Melanie; Maisto, Stephen A.; Lucke, Joseph F.; Brandon, Thomas H.; Eiden, Rina D.; Slosman, Kim S.; Giarratano, Paulette
Abstract: Introduction: Negative affect has been identified as a factor influencing continued smoking during pregnancy. In this study, a multi-component emotion regulation intervention was developed to address negative emotional smoking triggers and pilot-tested among low-income pregnant smokers. Treatment feasibility and acceptability, cotinine-verified rates of smoking cessation, and self-report of mean cigarettes smoked were assessed. Methods: Pregnant smokers who self-reported smoking in response to negative affect ( N = 70) were randomly assigned to receive one of two 8-session interventions: (1) emotion regulation treatment combined with standard cognitive-behavioral smoking cessation (ERT + CBT) or (2) a health and lifestyle plus standard smoking cessation active control (HLS + CBT). Outcomes for the 4-month period following the quit date are reported. Results: Treatment attendance and subjective ratings provide evidence for the feasibility and acceptability of the ERT + CBT intervention. Compared with the HLS + CBT control condition, the ERT + CBT condition demonstrated higher abstinence rates at 2 months (ERT + CBT = 23% vs. HLS + CBT = 0%, OR = 13.51; 95% CI = 0.70–261.59) and 4 months (ERT = 18% vs. HLS = 5%; OR = 2.98; 95% CI = 0.39–22.72) post-quit. Mean number of cigarettes per day was significantly lower in ERT + CBT at 2 months (ERT + CBT = 2.73 (3.35) vs. HLS + CBT = 5.84 (6.24); p = .05) but not at 4 months (ERT + CBT = 2.15 (3.17) vs. HLS + CBT = 5.18 (2.88); p = .06) post-quit. Conclusions: The development and initial test of the ERT + CBT intervention supports its feasibility and acceptability in this difficult-to-treat population. Further development and testing in a Stage II randomized clinical trial are warranted. Implications: Negative affect has been identified as a motivator for continued smoking during pregnancy. To date, smoking cessation interventions for pregnant smokers have not specifically addressed the role of negative affect as a smoking trigger. This treatment development pilot study provides support for the feasibility and acceptability of a multi-component ERT + CBT for low-income pregnant smokers who self-report smoking in response to negative affect. Study findings support further testing in a fully-powered Stage II efficacy trial powered to assess mediators and moderators of treatment effects.